27 Implementation, temporal changes, and follow-up of a nationwide AED-network. (21st May 2017) - Karlsson, LIM; Hansen, CM; Wissenberg, M; Hansen, SM; Lippert, FK; Rajan, S; Kragholm, K; Møller, S; Gislason, GH; Torp-Pedersen, C; Folke, F
Abstract : Aim: To describe the temporal development of automated external defibrillator (AED) deployment in Denmark according to type of AED location and accessibility. Methods: We collected information on all AEDs registered in the nationwide Danish AED network, 2007–2015, including type of AED location, accessibility 24 hours a day (24/7), and year of deployment. Results: The number of registered AEDs available for public access defibrillation increased from 140 in 2007 to 12 666 in 2015. In total, 14, 390 AEDs were registered during the study period. Of these, most AEDs were placed in companies/offices (29.3%, n=4, 213), followed by school/education facilities (12.6%, n=1, 819), and sport facilities (10.2%, n=1, 464) whereas few AEDs were deployed in residential areas (6.9%, n=999) and transportation facilities (1.0%, n=147). In 2007 and 2008, most AEDs were placed in sports facilities but then declined. From 2009 and forward, most AEDs were placed in companies/offices, whereas deployment in residential areas showed a temporal increase. AED accessibility 24/7 increased from 11.4% in 2007 to 35.2% in 2015, with residential areas having the highest 24/7 accessibility (83.2%, n=758), followed by churches/community centres (74.5%, n=301), and transportation facilities (69.0%, n=87). Despite AED deployment was highest in companies/offices only 14.8% (n=542) of these AEDs were accessible 24/7. Conclusion: The number of public available AEDs in Denmark has markedly increased from 2007–2015, with companies/offices, school/education facilities, and sport facilities as most frequent places of AED deployment. However, only 14.8% of AEDs placed at companies/offices had 24/7 accessibility. Conflict of interest: None declared. Funding: Dr. Karlsson is supported by a fund from The Danish foundation TrygFonden, who has no influence on study design; in the collection, analysis, or interpretation of data.